2004
DOI: 10.1128/aem.70.11.6767-6775.2004
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial Diversity and Function of Aerobic Granules Engineered in a Sequencing Batch Reactor for Phenol Degradation

Abstract: Aerobic granules are self-immobilized aggregates of microorganisms and represent a relatively new form of cell immobilization developed for biological wastewater treatment. In this study, both culture-based and cultureindependent techniques were used to investigate the bacterial diversity and function in aerobic phenol-degrading granules cultivated in a sequencing batch reactor. Denaturing gradient gel electrophoresis (DGGE) analysis of PCR-amplified 16S rRNA genes demonstrated a major shift in the microbial c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
75
1
3

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 121 publications
(84 citation statements)
references
References 46 publications
5
75
1
3
Order By: Relevance
“…One of the published studies describes the characterisation of a phenol degrading community present in aerobic granules, where the dominant degrader in the bioreactor was found to be a Pandoraea spp. Similarly to our study, this strain emerged as the fastest degrader and was stably maintained over the operating period (Jiang et al, 2004). Other studies also reported the degradation of aromatic compounds, such as p-xylene, 1,3-dihydroxybenzene and 2-chlorobenzoate (Bramucci et al, 2002;Demnerova et al, 2003;Matsui et al, 2006).…”
Section: Discussionsupporting
confidence: 76%
“…One of the published studies describes the characterisation of a phenol degrading community present in aerobic granules, where the dominant degrader in the bioreactor was found to be a Pandoraea spp. Similarly to our study, this strain emerged as the fastest degrader and was stably maintained over the operating period (Jiang et al, 2004). Other studies also reported the degradation of aromatic compounds, such as p-xylene, 1,3-dihydroxybenzene and 2-chlorobenzoate (Bramucci et al, 2002;Demnerova et al, 2003;Matsui et al, 2006).…”
Section: Discussionsupporting
confidence: 76%
“…The homology between band 11 and Anoxynatronum sibiricum was 88.1 %, whereas the homology between band 12 and Xanthomonas sp. PG-07 (Jiang et al 2004) and Xanthomonas axonopodis (Malik et al 2003) was 99.0 %. Furthermore, the homology between band 5 and the uncultured Cytophagales OPB56 was 90.6 %, and the homology between band 6 and the uncultured Planctomycete Clone T-RF20-23 was 90.4 %.…”
Section: Resultsmentioning
confidence: 96%
“…One likely reason accounting for the high degradation efficiency of granules that degrade phenol is the mass transfer barrier provided by a granule matrix that produces lower local phenol concentrations on cells than the bulk value (Liu and Tay, 2004). Jiang et al (2004b) isolated 10 bacterial strains from their aerobic phenol-degrading granules and identified their potential for degrading phenol. The PG-01 strain, a member of b-proteobacteria, is common in granules and is the predominant strain in phenol degradation.…”
Section: Introductionmentioning
confidence: 99%